Діяльність кредитних спілок на ринку фінансових послуг: стан, тенденції, перспективи. - Трусова, Наталя Вікторівна; Trusova, Natalia; Якушева І.Є., Радченко Н.Г (Мелітополь, ТДАТУ, 2021)
UKR: В роботі розглянуто основні аспекти функціонування кредитних спілок на вітчизняному ринку фінансових послуг, їх роль і задачі в сучасній фінансовій системі; проаналізовано стан розвитку, пробле ми діяльності та обґрунтовані напрямки активізації потенціалу кредитних спілок.//////// ENG: Credit unions are part of the country's financial system and an important participant in the financial ser vices market. Their main function is to provide deposit and credit and other related financial services to its members - individuals, small farms and farms, small businesses. In recent years, the number of credit unions and the scale of their activities have begun to decline rapidly, and this process continues. Financially unstable credit unions with a low level of management and bankrupt unions have disappeared from the financial services market. The remaining credit unions have relatively good performance and are the basis for further development of credit cooperation in Ukraine. The number of credit unions in 2019-2020 decreased by 15 units and the downward trend continues. Thus, in 2020, there were 322 credit unions in Ukraine, with 427 members. About 24.2% of members of credit unions had current loan agreements, 4.5% had deposits on deposit accounts. The scale of lending by the unions of its members for the analyzed period is increasing - in 2020 compared to the previous period by UAH 89.5 million. This is against the background of an increase in deposits of credit union members - 2.3 times compared to 2016, and 1.6 times compared to 2019. The advantages of credit unions as financial institutions are non-profit status, which helps reduce the overall cost of organizing its activities; lack of hidden interest and commissions that increase the total cost of consumers to service the loan. The cooperative nature of credit unions contributes to the interest of its members in effective cooperation, devel opment and reliability of the institution (that is the involvement of members of the credit union in its results). Besides it is possible to note democracy, interest, personalization in work of system of credit cooperation. The decline in the popularity of credit unions in the financial market of Ukraine is due to many reasons: low capi talization, limited customer base, low level of information technology, remote customer service opportunities, signifi cant financial risks (late and incomplete fulfillment of obligations to customers, lack of deposit guarantee system). Against this background, the unprofitability of credit unions is growing. The situation with the pandemic in 2020 made a negative contribution. Among non-bank financial institutions, credit unions proved to be the most vulnerable to quar antine restrictions. Effective development and intensification of credit unions in the market requires transformations in the credit coop eration market. First, it is the improvement of the regulatory framework based on a proportional approach; introduc tion and use of digitalization opportunities, wider online customer service of unions; attracting new participants - among the young, financially literate generation.
Activities of credit unions in the market of financial services: state, trends, prospects.
Keywords: кредитні спілки; інституційна структура ринку; ринок фінансових послуг; фінансування; фінансові інститути; фінансові ресурси; фінансові посередники; фінансові інструменти; фінансова інфраструктура; credit unions; financial services market; financial institutions; financial intermediaries; institutional structure of the marke; financial infra structure; financing; financial instruments; financial resources